DIMENSION 6 BIM IMPLEMENTATION (SUSTAINABILITY & EFFICIENCY) IN THE PROCUREMENT PROCUREMENT CYCLE GOODS & SERVICES - Arnoldus Jean Cornelis (Indonesian Journal of Multidisciplinary Science, 2022)
The application of the Building Information Model (BIM) method in a construction project, especially in Indonesia, can be counted as few who have implemented it in aligning the planning and implementation of a construction project activity, while if there is an application of the BIM concept, most of it is only as a formality only on the completeness of the Form document. of course, where the reality is that in practice there are many procedural deviations in creating an "Enviroment" of collaboration between work disciplines. In writing this paper, the problems will be analyzed: How is the process of implementing BIM in the 6D Dimension in the Supply Chain Cycle of the Procurement of Goods and Services problems. Writing based on this research has reference to knowledge base management, namely time management from references (eg PMBOK/Jurnal/BIM KEMENPUPR, etc.) and various relevant research results, literature review. This study uses the Fault Tree Analysis (FTA) method to answer the above problems. The results of this study are 1.. 2.. 3.. conclusions/research results. The analytical technique method that identifies system failures, the definition of failure is delay. The use of Top Down Analysis as a framework initially identifies and groups into Top Events in work delays, visualized into FTA graphics starting from Top Events to the most basic events.